Zwyczaje językowe w komunikacji grup internetowych na przykładzie forum rodzicielskiego = Language habits in the Internet groups communication on the example of Internet forum for parents - Idzikowska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article concerns the matter of communication in group of parents who share their pinions in Internet forums. A prime example is portal "Parenting.pl", defined as "modern dimension of parenthood". The estimated number of active users of mentioned portal is over one million per month. In Internet forums established as a maternal or parenting it is common that users who are associated with parenting experience express their individual opinions publically.
Keywords: internet; forum internetowe; grupy internetowe; parenting; macierzyństwo; komunikacja językowa; komunikacja internetowa; zwyczaje językowe; Internet forum; Internet groups; motherhood; language communication; Internet communication; language habits